Farmakologicheskaja i nutriciologicheskaja podderzhkafunkcii oporno-dvigatel'nogo apparatakvalificirovannyh sportsmenov - Gunina, L.; Dmitriev, A.; Yushkovskaya, O. (Science in Olympic Sport, 2018)
Objective. To develop a concept of the modern system of pathogenetically sound application of pharmacological preparations and dietary supplements for the prevention and treatment of joint diseases in elite athletes. Methods. Analysis and synthetic generalization of research and methodological literature, as well as the Internet re-sources that are relevant to the matter under study. Results. The data on the prevalence and the causes of joint disorders in highly qualifi ed athletes are presented. The categories of pharmacological and nutritional aids are described that are used in the world practice to prevent and treat such diseases in athletes. The emphasis was placed on the inappropriateness of the transfer of the treatment program for patients with rheumatoid arthritis to the system of prevention and treatment of joint disorders in athletes, where the development of this pathology is primarily mediated by a traumatic factor. The most common side effects of non-steroid anti-inflammatory drugs therapy most often used in such cases are described and current classification of these drugs is presented. The paper describes in detail supplementary aids of prevention and therapy for joint disorders using the nutritional supplements as well as provides the data on their eff ectiveness interms of evidence-based medicine. Conclusion. The approach of a sports doctor to the prevention and treatment of the pathology of the articular apparatus in athletes in terms of the application of the entire spectrum of necessary drugs and nutritional supplements should be comprehensive and should take into account the specifi cs of the sport, especially the anti-doping legislation that regulates the systemic, local, and intraarticular application of glucocorticoids